2019
DOI: 10.1111/his.13902
|View full text |Cite
|
Sign up to set email alerts
|

Histological analysis of fundic gland polyps secondary to PPI therapy

Abstract: Aims The aim of this study was to clarify the histopathological features of fundic gland polyps (FGPs) in patients treated with proton pump inhibitors (PPIs) and to investigate the mechanism of enlargement of FGPs after PPI treatment. Methods and results A total of 196 biopsy specimens of FGPs, which consisted of 87 FGPs in patients treated with PPIs (PPI group) and 109 FGPs in patients treated without PPIs (non‐PPI group) were compared histologically using haematoxylin and eosin staining, Ki67 immunohistochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 35 publications
2
27
1
1
Order By: Relevance
“…The maximum diameter of fundic gland cysts within the fundic gland polyps was larger in patients on PPI treatment than in those not receiving the drugs. 22 A retrospective study revealed three types of PPIassociated gastric polyps in chronic users, (1) fundic gland type,…”
Section: Ppi-related Histophatological Gastric Mucosal Changesmentioning
confidence: 99%
“…The maximum diameter of fundic gland cysts within the fundic gland polyps was larger in patients on PPI treatment than in those not receiving the drugs. 22 A retrospective study revealed three types of PPIassociated gastric polyps in chronic users, (1) fundic gland type,…”
Section: Ppi-related Histophatological Gastric Mucosal Changesmentioning
confidence: 99%
“…Pathologically, hyperplasia of parietal cells and parietal cell protrusion into the lumen are typical findings [3]. Although hypoacidity and hypergastrinemia increase the risk of gastric cancer in the corpus and fundus [4,5], the relationship between long-term PPI administration and tumor development remains unclear. Herein, we report the rare case of a 22 × 22 × 10 mm FGP in Helicobacter pylori (H. pylori)-uninfected gastric mucosa associated with long-term PPI administration that was mimicking gastric-type neoplasm and resected via endoscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Anyhow, PPI induced FGPs disappear when stopping treatment [ 127 , 128 ], for instance after anti-reflux surgery [ 129 ]. FGPs due to PPI treatment were reported to have higher percentage of proliferating cells assessed by Ki67 than other sporadic FGPs [ 130 ]. Similarly, three FGPs that were developed after 8 years of PPI therapy showed low grade dysplasia and in one adenocarcinoma [ 131 ].…”
Section: Gastric Polypsmentioning
confidence: 99%